Genes related to neural tube defects and glioblastoma - Rui Cao; Yurong Liu; Kaixin Wei; Ning Jin; Yuxiang Liang; Ruifang Ao; Weiwei Pan; Xiang Wang; Xiuwei Wang; Li Zhang; Jun Xie (Scientific Reports)
Abstract There are many similarities between early embryonic development and tumorigenesis. The occurrence of neural tube defects (NTDs) and glioblastoma (GBM) are both related to the abnormal development of neuroectodermal cells. To obtain genes related to both NTDs and GBM, as well as small molecule drugs with potential clinical application value. We performed bioinformatics analysis on transcriptome sequencing data of retinoic acid (RA)-induced NTDs mice, human NTDs samples and GBM samples. RT-qPCR, Western blot, and immunohistochemistry were used to validate the expression of candidate genes. Our results indicated that two genes at mRNA and protein levels have been well verified in both NTDs mouse and GBM human samples, namely, Poli and Fgf1. Molecular docking and validating in vitro were performed for FGF1 against pazopanib by using Autodock and Biacore. Cytological experiments showed that pazopanib significantly inhibited the proliferation of GBM tumor cells and mouse neural cells, promoted apoptosis, and had no effect on GBM tumor cells migration. Overall, our results demonstrated that Fgf1 abnormally expressed at different developmental stages, it may be a potentially prenatal biomarker for NTDs and potential therapeutic target for GBM. Pazopanib may be a new drug for the treatment of GBM tumors.